Online educational interventions in pediatric intensive care medicine - Daniel, Dennis; Wolbrink, Traci A. (Frontiers in Pediatrics, 2023)
Background Online education has experienced explosive growth, particularly in the wake of the COVID-19 pandemic. We explored the current state of the evidence base for online education targeted towards healthcare professionals working in pediatric intensive care units (PICUs), to report how we are using online education in our field. Materials and Methods We performed a literature review by systematically generating a list of publications indexed in PubMed describing online educational interventions in the PICU, using Medical Subject Header (MeSH)-based search terms and the following inclusion criteria: studies published after 2005 that describe online educational interventions aimed at healthcare professional working in the PICU. We reviewed the full text of all included articles, and summarized the study aims, design, and results. Results Our initial search yielded 1,071 unique articles. After screening abstracts and titles, then full texts, eight articles were included in the review. Many online learning modalities are represented, including websites, self-study modules, videos, videoconferencing, online self-assessment with feedback, virtual patient cases, screen-based simulation, and podcasts. Three studies focused on residents, two studies on nurses, two studies on a multidisciplinary team, and one study on transport nurses and paramedics. Most studies utilized participant surveys to assess satisfaction, and half included pre- and post-intervention multiple-choice question tests. Only one study included a patient-related outcome measure. Conclusions Despite growth in online medical educational intervention research, there are relatively few published studies in pediatric critical care, and only one study evaluated the impact of online learning on patient outcomes. There remain significant opportunities for PICU educators to assess the impact of online educational interventions, especially related to clinician behaviors and patient outcomes.